Behavioral characterization of ayahuasca treatment on Wistar rats in the open field test - Cid Pinheiro Farias; Paula Pólvora Victoria; Janaína Xavier; Fernanda Gelati Sekine; Eduardo Silveira Ribeiro; Giana de Paula Cognato; Hudson Wander Carvalho (Universidade de São Paulo, 2023)
Abstract Ayahuasca (AYA) is a psychedelic beverage with therapeutic potential for many mood and anxiety disorders. Although there are some preclinical studies, no published reports have tested the behavioral effects of AYA gavage in animal models. This investigation aimed to characterize the behavior of Wistar rats after acute ingestion of AYA for 40 min in the open field test (OFT). The sample consisted of three experimental groups treated with different dosages of AYA (125, 250, or 500 mg kg-1) and a control group. Each group consisted of 10 participants. After gavage, the number of crossings of the OFT grid lines, latency to enter the central area of the device, grooming frequency, and time spent in the central perimeter of the device were immediately evaluated. Analyses were based on one-way ANOVA and a linear-regression mixture model for longitudinal data. AYA intake did not interfere with habituation. The 500 mg kg-1 group showed a decrease in the time spent in the center of the device and in the number of crossings compared to the control group in the last 10 min. These results suggest that gavage with AYA did not interfere with the results, and the behavioral effects were perceived only between 30 and 40 min after gavage. Taken together, the results indicate that three aspects should be considered in OFT studies of AYA acute effects: the moment when the observation starts, the observation period, and the AYA dosage.